Do Cryptic Reservoirs Threaten Gambiense-Sleeping Sickness Elimination?. Issue 3 (March 2018) - Büscher, Philippe; Bart, Jean-Mathieu; Boelaert, Marleen; Bucheton, Bruno; Cecchi, Giuliano; Chitnis, Nakul; Courtin, David; Figueiredo, Luisa M.; Franco, José-Ramon; Grébaut, Pascal; Hasker, Epco; Ilboudo, Hamidou; et al.
Abstract : Trypanosoma brucei gambiense causes human African trypanosomiasis (HAT). Between 1990 and 2015, almost 440 000 cases were reported. Large-scale screening of populations at risk, drug donations, and efforts by national and international stakeholders have brought the epidemic under control with <2200 cases in 2016. The World Health Organization (WHO) has set the goals of gambiense -HAT elimination as a public health problem for 2020, and of interruption of transmission to humans for 2030. Latent human infections and possible animal reservoirs may challenge these goals. It remains largely unknown whether, and to what extend, they have an impact on gambiense -HAT transmission. We argue that a better understanding of the contribution of human and putative animal reservoirs to gambiense- HAT epidemiology is mandatory to inform elimination strategies. Highlights: gambiense -HAT is targeted for elimination with zero transmission in humans. Innovative tools may contribute to the achievement of elimination; these tools include rapid diagnostic tests, improved tsetse-control tools, and an oral drug to treat both stages of disease. Research is revealing associations between infection outcome, including self-cure, and mutations within genes involved in immune responses. Patient-derived T. b. gambiense strains can cycle in animals and tsetse flies without losing infectivity to humans. Molecular and serological techniques facilitate new studies on naturally infected animals as putative reservoir hosts. Mathematical modelling supports the hypothesis that human or animal reservoirs drive transmission, and they, or the tsetse vectors, could be targeted to swiftly impact transmission. Ongoing modelling will assess possible recrudescence via reservoirs.